2011
DOI: 10.1590/s1807-59322011000300003
|View full text |Cite
|
Sign up to set email alerts
|

Ocular findings in patients with systemic sclerosis

Abstract: OBJECTIVE: To evaluate the frequency and characteristics of ocular manifestations in outpatients with systemic sclerosis. METHODS: In this cross-sectional study, 45 patients with systemic sclerosis were enrolled. Data regarding demographics, disease duration and subtype, age at diagnosis, nailfold capillaroscopic pattern and autoantibody profile were collected, and a full ophthalmic examination was conducted. Parametric (Student's t-test) and nonparametric (Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 56 publications
4
47
1
2
Order By: Relevance
“…2 The most common ocular findings are keratoconjunktivitis sicca, eyelid skin fibrosis, anterior uveitis, normal tension glaucoma, optic neuropathy, and choroidopathy. [3][4][5][6] Choroid is a vascular structure of the eye that supplies oxygen and metabolites to the outer segment of the retina. 7 Enhanced depth imaging optical coherence tomography (EDI-OCT) technologies provide accurate quantitative analysis of the choroid tissue.…”
Section: Introductionmentioning
confidence: 99%
“…2 The most common ocular findings are keratoconjunktivitis sicca, eyelid skin fibrosis, anterior uveitis, normal tension glaucoma, optic neuropathy, and choroidopathy. [3][4][5][6] Choroid is a vascular structure of the eye that supplies oxygen and metabolites to the outer segment of the retina. 7 Enhanced depth imaging optical coherence tomography (EDI-OCT) technologies provide accurate quantitative analysis of the choroid tissue.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most frequent ocular features of SSc is dry eye disease (DED), which has been identified to occur in 37-79% of patients and is thought to be derived from fibrosis of the conjunctiva and lacrimal gland, which leads to a tear deficiency state that causes further damage to the ocular surface [4,5]. Although the probability of dry eye causing blindness or visual impairment is low, it has a significant impact on the daily and social lives of patients [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the frequency of eyelid skin changes is expected to be different in ssSSc patients due to the absence of skin thickening, but no prevalence studies are known. In the previous study, recurrent episcleritis was reported (4.4%), but other inflammatory diseases, including scleritis, peripheral ulcerative keratitis and uveitis, were not (13). To our knowledge, there are only four case reports in the literature pointing to a rare association between SSc and uveitis in adults, since this relationship is more established in pediatric scleroderma (9,14).…”
Section: N Discussionmentioning
confidence: 85%
“…In a cross-sectional study of 25 patients, eyelid skin changes were present in the majority (51.1%), keratoconjunctivitis sicca in almost half (48.9%), cataracts in 42.2%, retinal microvascular abnormalities (indistinguishable from those related to systemic hypertension and often associated with a severe capillaroscopic pattern) in 28.9%, glaucoma in 13.3% and conjunctival vascular congestion in 8.9% (13). Furthermore, microcirculation seems to be affected early in the course of the disease, with significant reduction of choroidal perfusion (8).…”
Section: N Discussionmentioning
confidence: 99%